Iklim Investasi di Indonesia - Lu Sudirman (Jurnal Selat, 2016)
The development of Indonesia’s economy has been going for more or less 46 years since it was launched by the government of the New Order on 1970. With a period of more than half a century has brought changes in the life of Indonesians that was done by the development of economy with various escalation and dynamics. Making a development will surely need a large amount of capital and provided at the right tims. Capital can be provided by the government and by the wide society, especially in the private business world. An ideal situation, in terms of nationalism is that if the need of the capital itself can be fully provided by the ability of capital in it’s own country, whether it be the government and or the world of the country’s private business. But in reality, developing countries in terms of the ability of providing enough capital to develop As a whole experience various difficulties that is caused by various factors, that is; low rates of the society’s savings, a not effective and not efficient accumulation of capital, the inadequate skills and the technology. Keyword: foreign capital investment, foreign investor in Indonesia, and influenced factors